Management of pasireotide-induced hyperglycemia in patients with acromegaly: An experts’ consensus statement - Störmann, Sylvère; Meyhöfer, Sebastian M.; Groener, Jan B.; Faust, Johanna; Schilbach, Katharina; Seufert, Jochen; Vergès, Bruno (Frontiers in Endocrinology, 2024)
Pasireotide is a somatostatin analogue for the treatment of acromegaly, a chronic condition caused by excess growth hormone. Despite the therapeutic benefits of pasireotide as a second-line treatment for inadequately controlled acromegaly, a major concern is its hyperglycemic side-effect. Here, we provide guidance on how to select appropriate patients with acromegaly for treatment with pasireotide. We summarize baseline characteristics of patients at high risk for pasireotide-associated hyperglycemia and recommend a monitoring strategy based on the risk profile. Self-monitoring of blood glucose levels (SMBG), measurements of fasting plasma glucose (FPG), postprandial plasma glucose (PPG) and regular HbA1c measurements are the foundation of our proposed monitoring approach. The pathophysiology of pasireotide-induced hyperglycemia involves decreased secretion of the incretin hormones GIP (glucose-dependent insulinotropic polypeptide) and GLP-1 (glucagonlike peptide-1). Our expert recommendations address the specific pathophysiology of pasireotideinduced hyperglycemia by recommending the incretin-based therapeutics dipeptidyl peptidase-4 inhibitors (DPP-4i) and glucagon-like peptide-1 receptor agonists (GLP-1 RA) in all appropriate patients as an alternative to first-line monotherapy with metformin. Furthermore, we emphasize the importance of adequate control of acromegaly, excellent diabetes education, nutrition and lifestyle guidance and advise to consult expert diabetologists in case of uncertainty in the management of patients with hyperglycemia under pasireotide.